Decision to cast a vote: an ordinal regression statistical analysis - Lubis, Muharman; Kartiwi, Mira; Zulhuda, Sonny (2014)
This paper aims to explore on essential factor, which influence the decision of eligible voters to cast vote in general election. We use the Indonesia as the setting and targeted specific demographic data to see whether the diversity and geographic affect the decision to case vote such as gender, age, working, education and earnings. By understanding the characteristic of eligible voters are important to determine the information system that will be used in electronic voting as well to drafting the relevant regulation. It will bridge the gaps occurred between government understanding and citizen expectation, so the solution not only comes from the external factor but also internal. As the goals, this study will contribute to privacy protection schema for future electronic voting which has been planed to take place in the next election. In this study, ordinal regression will be used to measure the tendency and direction of the demographic data from citizen towards the social norm items.